Epstein-Barr Virus (EBV)-Infected Monocytes Facilitate Dissemination of EBV within the Oral Mucosal Epithelium - Tugizov, Sharof (American Society for Microbiology, 2007)
Epstein-Barr virus (EBV) causes hairy leukoplakia (HL), a benign lesion of oral epithelium that occurs primarily in the setting of human immunodeficiency virus (HIV)-associated immunodeficiency. However, the mechanisms of EBV infection of oral epithelium are poorly understood. Analysis of HL tissues shows a small number of EBV-positive intraepithelial macrophages and dendritic/Langerhans cells. To investigate a role for these cells in spreading EBV to epithelial cells, we used tongue and buccal explants infected ex vivo with EBV. We showed that EBV first infects submucosal CD14(+) monocytes, which then migrate into the epithelium and spread virus to oral epithelial cells, initiating productive viral infection within the terminally differentiated spinosum and granulosum layers. Incubation of EBV-infected monocytes and oral explants with antibodies to CCR2 receptor and monocyte chemotactic protein 1 prevented entry of monocytes into the epithelium and inhibited EBV infection of keratinocytes. B lymphocytes played little part in the spread of EBV to keratinocytes in our explant model. However, cocultivation of EBV-infected B lymphocytes with uninfected monocytes in vitro showed that EBV may spread from B lymphocytes to monocytes. Circulating EBV-positive monocytes were detected in most HIV-infected individuals, consistent with a model in which EBV may be spread from B lymphocytes to monocytes, which then enter the epithelium and initiate productive viral infection of keratinocytes.